Functional roles of raffinose family oligosaccharides: Arabidopsis case studies in seed physiology, biotic stress and novel carbohydrate engineering - Loedolff, Bianke (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.